Redução de microrganismos indicadores, vírus entéricos e SARS-CoV-2 presentes em efluente de reator UASB através de tratamento térmico utilizando coletor solar - Lorena Aparecida Noia Menezes (2022)
The objective of the present work was to evaluate the microbiological quality of sewage produced by treatment with a UASB reactor, followed by solar thermal disinfection, with regard to the reduction of pathogen indicators, enteric viruses and Sars-Cov-2. During the period from August to October 2021, 10 disinfection trials were carried out. The UASB reactor whose effluent was collected and used in the experimental disinfection unit received predominantly domestic sewage and is located at the Sanitation Research and Training Center (CePTS) - UFMG/COPASA, installed inside the Ribeirão Arrudas Sewage Treatment Station, belonging to to COPASA (Sanitation Company of Minas Gerais). The solar thermal disinfection study was carried out on the premises of the Pampulha campus of the Federal University of Minas Gerais (UFMG), in the city of Belo Horizonte. The disinfection apparatus was operated in batches with cycles of 8 hours and consists of commercial solar collectors, adapted to receive a total volume of 36 liters, composed of a set of three collector tubes (absorbers) with vacuum operation, connected directly to a thermal reservoir (boiler). The temperature of the liquid was monitored using RC-4 data logger which, a sensor positioned inside the boiler, measured and recorded the effluent temperature every 15 minutes. The microbiological investigation was performed by analyzing Coliforms, E. coli and somatic coliphages, while viral quantification was performed via qPCR and RT-qPCR and viral viability analysis was performed by cell culture method. In addition, physicochemical parameters such as pH, COD and solids series were monitored. The best performance of the system was observed in tests carried out with average solar radiation above 1,050 KJ/m², which were the days of open sky, in which the average temperature of the effluent was always above 40°C. In these cases, reduction efficiencies of E. coli and total coliforms of up to 4.38 log10 and 4.72 log10, respectively, were achieved, while somatic coliphages were more resistant to treatment, with reductions of 2.32 log10. The results related to the viral investigation by qPCR showed no significant difference between the concentration values at the entrance and exit of the disinfection system. However, the fact that the genetic material of the viruses of interest was not removed does not mean that there was no inactivation of these viruses in the samples evaluated.